2021
DOI: 10.3389/fphar.2021.758763
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy With Rapamycin and Low Dose Imatinib in Pulmonary Hypertension

Abstract: Rationale: Enhanced proliferation and distal migration of human pulmonary arterial smooth muscle cells (hPASMCs) both contribute to the progressive increases in pulmonary vascular remodeling and resistance in pulmonary arterial hypertension (PAH). Our previous studies revealed that Rictor deletion, to disrupt mTOR Complex 2 (mTORC2), over longer periods result in a paradoxical rise in platelet-derived growth factor receptor (PDGFR) expression in PASMCs. Thus, the purpose of this study was to evaluate the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Significant published work has accumulated, demonstrating that as in cancer, there is a critical metabolic component to PH development ( 38 , 39 ). Whether metabolic dysfunction precedes PAH development or is a consequence (or partly both ways) remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Significant published work has accumulated, demonstrating that as in cancer, there is a critical metabolic component to PH development ( 38 , 39 ). Whether metabolic dysfunction precedes PAH development or is a consequence (or partly both ways) remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism of autophagy is complex and is regulated by various signaling pathways [ 46 ]. Particularly, the ERK1/2-Beclin-1 and PI3K-AKT-mTOR signaling pathways have been proven to regulate autophagy and the proliferation of PASMCs [ 53 55 ]. In this study, we found that both of these signaling pathways were stimulated.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapies could also be of interest. A low dose combination of Imatinib with Rapamycin attenuated PH, reducing RVSP, right ventricle hypertrophy and vessels muscularization, in MCT and SU5416/CH rats [ 108 ].…”
Section: Potential Future Therapies Targeting the Pdgf Pathway In Pah...mentioning
confidence: 99%